1982
DOI: 10.1128/jcm.15.4.660-662.1982
|View full text |Cite
|
Sign up to set email alerts
|

Comparative measurement of equine influenza virus antibodies in horse sera by single radial hemolysis, neutralization, and hemagglutination inhibition tests

Abstract: Single radial hemolysis (SRH), neutralization (NT), and hemagglutination inhibition (HI) tests were carried out on sera from horses immunized against the Prague and Miami strains of equine influenza virus. The HI and NT tests demonstrated good sensitivity; the sensitivity of the SRH test was somewhat lower. The NT titers of individual sera were correlated very closely with the HI titers, although the NT titers were higher. SRH zone diameters of individual sera also showed significant correlation with the NT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 2 publications
2
10
1
Order By: Relevance
“…11,14,28 The correlation between SRH and MN assays observed in this study is in agreement with the findings of the previous studies that used equine influenza strains and H3N2 influenza strain. 11,29,30 However, unlike Wang et al, 30 who found much higher correlations between SRH and MN assays than between SRH-HI and HI-MN assays, we found no significant differences among them. The correlation among the three assays was also evaluated for influenza B strains (Victoria and Yamagata lineages), showing good agreement.…”
Section: F I G U R E 1 Continuedcontrasting
confidence: 99%
See 2 more Smart Citations
“…11,14,28 The correlation between SRH and MN assays observed in this study is in agreement with the findings of the previous studies that used equine influenza strains and H3N2 influenza strain. 11,29,30 However, unlike Wang et al, 30 who found much higher correlations between SRH and MN assays than between SRH-HI and HI-MN assays, we found no significant differences among them. The correlation among the three assays was also evaluated for influenza B strains (Victoria and Yamagata lineages), showing good agreement.…”
Section: F I G U R E 1 Continuedcontrasting
confidence: 99%
“…In addition, the assay agreement on protection, as defined by 11,29,30,33 Previous studies involving A strains support the strong agreement between HI and SRH assays found in present study. 11,14,28 The correlation between SRH and MN assays observed in this study is in agreement with the findings of the previous studies that used equine influenza strains and H3N2 influenza strain.…”
Section: F I G U R E 1 Continuedsupporting
confidence: 90%
See 1 more Smart Citation
“…We found the SRH assay to be less sensitive than the MN assay but more sensitive than HAI, as 16% of participants had SRH titres below 11,12 suggest that SRH may be more sensitive for detecting antibodies against influenza B than influenza A viruses, while the study by Yamagishi et al 10 suggests that the sensitivity of SRH test is lower than that of HAI, at least for equine influenza virus.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, SRH is the serological test of choice for measuring vaccine efficacy. Few studies, however, have compared EI serological techniques during outbreaks [ 46 , 47 ]. Similar to the findings by Morley et al [ 46 ], a good correlation between the HI and SRH test was observed in this study, although SRH demonstrated greater diagnostic sensitivity.…”
Section: Discussionmentioning
confidence: 99%